Usage thérapeutique du manguier (Mangifera indica L., Anacardiaceae) au Burkina Faso - Corneille Drabo; Zara Soutonnoma Nikiema; Oumarou Zoéyandé Dianda; Abdalla Dao; Jacob Sanou; Mahamadou Sawadogo (VertigO, 2023)
Mango (Mangifera indica L., Anacardiacaea) organ extracts have potential use in pharmaceutical applications. The aim of this study is to contribute to a better knowledge of mango health benefits in Burkina Faso. Ethnobotanical surveys were carried out using a questionnaire among herbalists in three regions of Burkina Faso (Centre-Ouest, Hauts-Bassins and Cascades). The results were obtained from 45 herbalists surveyed. These herbalists are represented by 79% men and 21% women. The age group between 31 and 40 years is the most represented, i.e. 32.41%, and 59.25% of the herbalists surveyed are illiterate. The results obtained made it possible to list the diseases commonly treated with mango organs. Moreover, mango leaves of the ordinary varieties (green mango and saber) are the most used in the preparation of medicines. Decoction is the most popular method of preparation and the remedies are administered by oral route (100%). A pharmacological study should make it possible to incorporate extracts of mango organs into food supplements to treat diseases.